Physicochemical characteristics of stingless bee honey from Heterotrigona itama sp. / Nur Syamimi Ismail - Ismail, Nur Syamimi (2019)
The purpose of this study is to investigate the physicochemical characteristics of Malaysian stingless bee honey from Heterotrigona itama species. The aim of this study is to provide as much information about stingless bees and can be used by subsequent researchers to conduct more analysis of stingless bees. Several parameters have been performed to obtain data on the physicochemical characteristics of stingless bee from Heterotrigona itama species. The physicochemical characteristics were pH, ash content, total acidity, color intensity, and moisture content. Honey produced by Heterotrigona itama sp. is taken randomly from five different logs. The results reveal the pH values of stingless bees are range 3.32±0.01 to 3.60±0.01 which is known as acidic. The colour intensity ranged from 35-50 mm Pfund (extra light amber). The ash content and acidity value of stingless bee honey samples ranged from 0.127±0.061 to 0.413±0.022 g/100g and 109±7.81 to 135±8.66 meq/kg. The moisture content ranged from 23.00±0.50 to 26.83±0.29 %. Clearly, honey produced by a stingless bee from Heterotrigona itama sp. has similar physicochemical characteristics although the honey sample taken from different places.